Astronomy with a Budget Telescope An Introduction to Practical Observing - Moore, Patrick; Watson, John.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
If you had purchased an inexpensive astronomical telescope a few years ago, disappointment would have been almost guaranteed. In current Internet age, times have changed and most (but not quite all) telescopes have been used to favorable results. Sir Patrick Moore, working with John Watson, has surveyed and tested the best and the worst of today's budget-priced astronomical telescopes. This new edition of Astronomy with a Budget Telescope is the result of their efforts. This book will show you how to recognize the good from the bad in observational ware with essential hints and tips on what to look for when buying both new and used telescopes. Updated and expanded, this latest edition includes budgeting tips for the new generation of digital cameras and 'go-to' telescopes. It provides a step-by-step guide to setting up your telescope, and how to observe the Moon, Sun, planets, stars, nebulae, and galaxies. Inside you'll find full-page finder charts and full-color images showing you what each object should look like. Astronomy with a Budget Telescope, 2nd Edition, is the complete introduction to buying and using a low-cost amateur astronomical telescope!
How to Buy a Budget Telescope -- How to Use a Budget Telescope -- Observing the Solar System -- Observing the Stars and Galaxies -- Photography and Imaging -- Image Processing Software -- Trying Out Two Typical Budget Telescopes -- The Next Steps.
Keywords: Physics; Physics; Astronomy, Observations and Techniques